HUBUNGAN POSISI DUDUK TERHADAP KELUHAN LOW BACK PAIN PADA PEKERJA MAL CINERE TAHUN 2021 - Alif Putra Suryaprobo, (2021)
Lower Back Pain is a disease where pain occurs in the lower back area, one of which is caused by incorrect sitting position. The purpose of this study was to analyze the relationship between sitting position and internal factors such as age, gender, smoking status, physical activity, BMI, years of service to symptoms of Lower Back Pain in Cinere Mall workers. This study uses quantitative analytical methods with a cross sectional study design. The sampling technique used is total sampling so that the respondents in this study amounted to 50 people. The results of the chi square test showed that there was a relationship between age (p value 0.005 <0.05), BMI (p value 0.010 <0.05), physical activity (p value 0.040 <0.05), sitting position (p-value 0.043 <0.05) with symptoms of Lower Back Pain and there is no relationship between years of service (p-value 0.794> 0.05), gender (p value 0.943> 0.05), smoking status (p-value 0.927> 0.05) with symptoms of Lower Back Pain. The conclusion of this study is that there is a relationship between age, BMI, physical activity, sitting position where complaints of Lower Back Pain exist. Therefore, it is recommended that workers pay more attention to their health, including paying attention to their daily sitting position in order to reduce the possibility of muscle fatigue caused by a static position at work.